The mind of the leader : how to lead yourself, your people, and your organization for extraordinary results - Hougaard, Rasmus; Carter, Jacqueline (Boston Harvard Business Review Press, 2018)
Most leaders think they're effective at motivating their employees, but study after study shows that employees are more disengaged and uninspired than ever. The solution lies not in more management training or fun off-sites but in looking within--into the mind of the leader. Based on their years-long research and practice, Rasmus Hougaard and Jacqueline Carter, of the Potential Project, have conclusively found that three qualities stand out as being foundational for leaders today: mindfulness, selflessness, and compassion--what they call the MSC Leadership Mind, the ideal mind of the leader. Mindfulness addresses the distractedness that kills our focus, stunts our productivity, and makes us action-addicted multitaskers. Selflessness addresses the general lack of fulfillment in work life by helping us--and the people we lead--find true happiness and meaning. And compassion addresses today's social disintegration by enhancing true human connections, followership, and engagement. While some think these traits are innate, Hougaard and Carter, together with hundreds of their associates working with thousands of leaders around the world, have developed a system to help leaders of all kinds learn and cultivate the MSC Leadership Mind. By addressing their own needs first, then those of their people, and finally the culture of their organization, every leader can learn to embody what makes for great leadership in today's challenging organizational environment.--
Keywords: Leadership; Mindfulness (Psychology); Selflessness (Psychology); Compassion